2021
DOI: 10.3390/ijms22094799
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in Acute ST Elevation Myocardial Infarction—A New Tool for Diagnosis and Prognosis: Therapeutic Implications

Abstract: Despite diagnostic and therapeutic advances, coronary artery disease and especially its extreme manifestation, ST elevation myocardial infarction (STEMI), remain the leading causes of morbidity and mortality worldwide. Early and prompt diagnosis is of great importance regarding the prognosis of STEMI patients. In recent years, microRNAs (miRNAs) have emerged as promising tools involved in many pathophysiological processes in various fields, including cardiovascular diseases. In acute coronary syndromes (ACS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 148 publications
(242 reference statements)
0
20
0
Order By: Relevance
“…As observed, they detain key functions in cardiac biogenesis, development, and progression, and given their stable structure and rapid circulation release after myocardial injury, they were proposed as potential future biomarkers in ACS. More specifically, older and recent evidence point out the potential role of miRNAs as novel biomarkers not only in STEMI, but also in STEMI's secondary complication such as LVR or HF (Table 1), , or even their use as promising new therapeutic targets [180,181] (Table 2). More than that, miRNAs have the potential to be used in the differential diagnosis of ACS [17,182] with: unstable angina [183], NSTEMI [94,184], and acute myocarditis [185].…”
Section: Discussionmentioning
confidence: 99%
“…As observed, they detain key functions in cardiac biogenesis, development, and progression, and given their stable structure and rapid circulation release after myocardial injury, they were proposed as potential future biomarkers in ACS. More specifically, older and recent evidence point out the potential role of miRNAs as novel biomarkers not only in STEMI, but also in STEMI's secondary complication such as LVR or HF (Table 1), , or even their use as promising new therapeutic targets [180,181] (Table 2). More than that, miRNAs have the potential to be used in the differential diagnosis of ACS [17,182] with: unstable angina [183], NSTEMI [94,184], and acute myocarditis [185].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, miR-133a has been shown to have beneficial effects on infarcted hearts by inhibiting inflammation and angiogenesis via FGFR1 and VEGFR2 signaling pathways ( 82 , 83 ). Similarly, miR-320 and miR-144-3p, have been shown to be involved in post-MI responses by regulating PTEN/PI3K/Akt signaling pathway ( 13 , 84 , 85 ); miR-144-3p promotes cardiac fibrosis via targeting PTEN following MI ( 14 ); miR-199a-3p and miR-590-3p also improve cardiac function after MI ( 8 , 86 ); miR-19a/19b inhibits the inflammatory response and has been shown to enhance cardiac function post-MI by targeting Bim1 and PTEN ( 8 ). All these results are relevant when considering that in vivo studies carried out in infarcted mice revealed that angiogenesis can be improved by inhibiting PTEN via activating the PI3K/Akt/VEGF pathway ( 13 , 87 , 88 ).…”
Section: Cardiac Inflammation and Micrornasmentioning
confidence: 99%
“…The nature of the hyperglycemic damage in patients affected by DM lies in the accumulation of superoxide anions, which are free radicals capable of activating cellular pathways that includes advanced glycation end products (AGEs), polyol and hexosamine flux, PKC, and vascular inflammation mediated by nuclear factor-B. Hyperglycemia itself also increases oxidative stress through greater glucose oxidation in the citric acid cycle (14) . All these different hyperglycemia consequences lead to decreased cellular resistance to oxidative stress, amplification of the proinflammatory response, and apoptosis of endothelial cells and their overall dysfunction.…”
Section: Cardiovascular Risk Factors and Ischemic Heartmentioning
confidence: 99%